MiPlato para Adultos Mayores - Linda B. Bobroff (EDIS)
Adultes mayores: ¿Qué hay en su plato? This full color handout is the Spanish-language version of FCS8993/FY1260: My Plate for Older Adults, and was adapted from USDA's MyPlate by nutrition faculty of the UF Department of Family, Youth and Community Sciences, October 2011.